Nexus of Ethical Leadership, Career Satisfaction, Job Embeddedness, and Work Engagement in Hospitality Industry: A Sequential Mediation Assessment - Khattak, Shoukat Iqbal; Haider, Aftab; Ahmed, Syed Khalil; Rizvi, Syed Tahir Hussain; Shaokang, Lin (Frontiers in Psychology, 2022)
The purpose of this paper is to propose a research model in which job embeddedness and work engagement sequentially mediate the effects of ethical leadership on career satisfaction. It also aims to test whether job embeddedness heightens WENG which is indirectly influenced by ethical practices ending in employees’ satisfaction. This paper used time-lagged data collection procedure and documented 247 responses from hotel employees in Pakistan. For data analysis, the structural equation modeling was used to measure and evaluate the links among the aforementioned constructs. The study empirically identified that employees are high on WENG once they are treated with ethical leadership style supplementing their sense of job embeddedness and hence found to be satisfied on career paths. This research paper adds value to the literature on hospitality industry by addressing the calls for research and pinned multiple mediators (i.e., job embeddedness and work engagement) between ethical leadership and career satisfaction. The extant study also checked the effect of supervisors’ ethical behaviors regarding career satisfaction among the employees of Pakistani hotel industry. Based on such contribution, this study focused on exploring the underlying mechanisms through attitude theory and thus, aims to fill in these voids.